NF2 Activates Hippo Signaling and Promotes Ischemia/Reperfusion Injury in the Heart. Issue 5 (19th August 2016) - Matsuda, Takahisa; Zhai, Peiyong; Sciarretta, Sebastiano; Zhang, Yu; Jeong, Jae Im; Ikeda, Shohei; Park, Jiyeon; Hsu, Chiao-Po; Tian, Bin; Pan, Duojia; Sadoshima, Junichi; Del Re, Dominic P.
Abstract : Rationale: : NF2 (neurofibromin 2) is an established tumor suppressor that promotes apoptosis and inhibits growth in a variety of cell types, yet its function in cardiomyocytes remains largely unknown. Objective: : We sought to determine the role of NF2 in cardiomyocyte apoptosis and ischemia/reperfusion (I/R) injury in the heart. Methods and Results: : We investigated the function of NF2 in isolated cardiomyocytes and mouse myocardium at baseline and in response to oxidative stress. NF2 was activated in cardiomyocytes subjected to H2 O2 and in murine hearts subjected to I/R. Increased NF2 expression promoted the activation of Mst1 (mammalian sterile 20–like kinase 1) and the inhibition of Yap (Yes-associated protein), whereas knockdown of NF2 attenuated these responses after oxidative stress. NF2 increased the apoptosis of cardiomyocytes that appeared dependent on Mst1 activity. Mice deficient for NF2 in cardiomyocytes, NF2 cardiomyocyte-specific knockout (CKO), were protected against global I/R ex vivo and showed improved cardiac functional recovery. Moreover, NF2 cardiomyocyte-specific knockout mice were protected against I/R injury in vivo and showed the upregulation of Yap target gene expression. Mechanistically, we observed nuclear association between NF2 and its activator MYPT-1 (myosin phosphatase target subunit 1) in cardiomyocytes, and a subpopulation of stress-induced nuclear Mst1 was diminished in NF2 CKO hearts. Finally, mice deficient for both NF2 and Yap failed to show protection against I/R indicating that Yap is an important target of NF2 in the adult heart. Conclusions: : NF2 is activated by oxidative stress in cardiomyocytes and mouse myocardium and facilitates apoptosis. NF2 promotes I/R injury through the activation of Mst1 and inhibition of Yap, thereby regulating Hippo signaling in the adult heart. Abstract : Supplemental Digital Content is available in the text.